Bandgap Engineering of Cesium Lead Halide Perovskite CsPbBr3 through Cu Doping. Issue 10 (27th July 2022) - Wu, Qiaoqian; Li, Jinping; Xue, Shaoming; Zhao, Yiting; Liu, Fangchao; Huo, Qiuhong; Mi, Jun; Guan, ChengBo; Cong, Wei‐Yan; Lu, Ying‐Bo; Ren, Junfeng
Abstract: Cu‐doped CsPbBr3 with strong blue emissions is a potentially ideal material for high‐quality light‐emitting diode (LED) devices. This study thoroughly analyzes the influence of a Cu dopant on CsPbBr3 materials through a series of theoretical investigations. Two artificial CsPbBr3 supercells are constructed, and their electronic properties are analyzed. Additionally, the antibonding nature of the conduction band minimum (CBM) and valance band maximum (VBM) of CsPbBr3 is elucidated. The results indicate that a Cu dopant can only alter the local lattice around it, not the entire lattice. Moreover, the CBM and VBM deformation potentials of CsPbBr3 behave differently. Therefore, the energetic shift of VBM is more sensitive to the shrinkage of lattice due to the smaller energy difference between the constituent orbitals, leading to a bandgap reduction with the lattice contraction. This study reveals that the two critical reasons for the increase of bandgap are the contribution of Cu‐3d orbitals to the VBM and the localized lattice distortion caused by Cu impurity. Therefore, this work clarifies how Cu impurities improve the blue light emitting performance of CsPbBr3 systems. Abstract : This work clarifies how Cu‐doped CsPbBr3 is a potential ideal blue light‐emitting diode (LED) material. It is revealed that Cu induces localized lattice distortion and affects bonding interactions which influences the near band edge structures in CsPbBr3 . These two critical factors cause an increase of bandgap and blueshift of light emitting in Cu‐doped CsPbBr3 .